Motivation in Dhamma Pracetice of Buddhists at Wat Thongnaim, Nongkhaem District, Bangkok - Xaysomebath, Phramaha Phouthasone; Ruksat, Suvin; Guttaviro, Phramaha Viroj (Journal of Thammawat, 2024)
The purpose of this article was: 1) to study the motivation for practicing Dhamma of Buddhists at Wat Thong Niam, Nong Khaem District, Bangkok; 2) to compare the motivation for practicing Dhamma of Buddhists at Wat Thong Niam; 3) to study suggestions regarding the motivation for practicing Dharma among Buddhists at Wat Thong Niam. The sample group was 130 people. The instrument used was a questionnaire. The statistics used for data analysis are frequency, percentage, mean, standard deviation, t-test, and one-way ANOVA. The analysis of mean differences for pairs was done using Scheffe's method (Post Hoc). The research results found that: 1) the motivation data for practicing Dhamma of Buddhists at Wat Thong Niam were at a high level overall (= 3.86). When considering each aspect, it was found that the need for happiness and peace of mind had the highest mean (= 4.33), followed by the aspect of accommodation (= 4.18), and the need for security and safety had the lowest mean (= 3.09), respectively. 2) The results of the comparison of the motivation data for practicing Dhamma of Buddhists at Wat Thong Niam with different genders, ages, education levels, and experiences in practicing Dhamma showed that the motivation for practicing Dhamma of Buddhists at Wat Thong Niam was not significantly different at the .05 level. 3) Suggestions for the motivation for practicing Dhamma of Buddhists at Wat Thong Niam regarding the use of communication tools during the practice, the number of monks who are lecturers is not sufficient for the operation and there is not a variety, the installation of air conditioners in the practice area that make the practitioners comfortable during the practice because the temperature is not suitable enough, and the preparation of the practitioners' accommodation and bathrooms are not yet complete.